Dose Finding of Lenvatinib in Subjects With Advanced Hepatocellular Carcinoma Based on Population Pharmacokinetic and Exposure–Response Analyses. (31st May 2017) - Tamai, Toshiyuki; Hayato, Seiichi; Hojo, Seiichiro; Suzuki, Takuya; Okusaka, Takuji; Ikeda, Kenji; Kumada, Hiromitsu
Abstract: Hepatocellular carcinoma (HCC) accounts for up to 90% of primary liver cancer occurrences worldwide. Lenvatinib, a multikinase inhibitor, was approved in radioiodine‐refractory differentiated thyroid cancer. In this phase 2 study (study 202), we aimed to identify the lenvatinib optimal dose for subjects with advanced HCC Child‐Pugh class A. Pooled data from phase 1 studies in healthy adults and in subjects with mixed tumor types, and from study 202 in subjects with HCC, were analyzed using a population pharmacokinetic approach. The relationship between treatment‐emergent adverse events leading to withdrawal or dose reduction during cycle 1 and lenvatinib exposure was explored by logistic regression analysis. A receiver operating characteristics analysis was used to investigate the best cutoff values of lenvatinib exposure and body weight to identify a high‐risk group for early dose modification. The final pharmacokinetic model included body‐weight effects on apparent clearance and volume. The relationship between the lenvatinib area under the plasma concentration–time curve (AUC) at steady state and body weight demonstrated an increase in AUC as body weight decreased in subjects with HCC. An exposure–response relationship was observed, with higher lenvatinib AUC and lower body weight resulting in earlier drug withdrawal or dose reduction. The best cutoff values for body weight and lenvatinib AUC were 57.8 kg and 2430 ng·h/mL, respectively, to predict the group at high risk for early drug withdrawal or dose reduction. We therefore recommend 12‐mg and 8‐mg starting doses for subjects ≥60 kg and <60 kg, respectively, in subjects with HCC Child‐Pugh class A.